Yurisdiksi Negara Pantai Terhadap Kapal Asing Yang Memuat Limbah Bahan Berbahaya Dan Beracun (B3) Ditinjau Dari Hukum Laut Internasional - Djunaidi, Muhamad Renaldy; Tuhulele, Popi; Daties, Dyah Ridhul Airin (Faculty of Law Pattimura University, 2023)
Introduction: The jurisdiction of the coastal state is an authority of the state to carry out laws and regulations in its territorial area to regulate people, property, and events that occur in the land area, sea waters, and air space above it.Methods of the Research: The research method used is normative juridical. by using a problem approach such as a statutory approach, a conceptual approach and a case approach. While the sources of legal materials used are primary, secondary and tertiary sources of legal materials. The collection of legal materials is carried out by means of a literature study, then analyzed qualitatively. Results of the Research: The results show that the entry of foreign ships transporting waste in the jurisdiction of the coastal state is not prohibited as long as it is subject to the provisions for the transportation of hazardous and toxic waste that is passing through the territory of the coastal state, namely for foreign ships carrying nuclear or other goods which because of their nature dangerous or toxic, if you want to make a voyage in the territorial waters of an International country, you must carry documents and comply with special precautions established by International treaties for ships (Article 23 of the 1982 International Law Of The Sea Convention). The implementation of Indonesian Jurisdiction for foreign ships transporting waste has been regulated in Law Number 17 of 2008 concerning Shipping and Government Regulation Number 101 of 2014 concerning Management of Hazardous and Toxic Waste, which explains all matters relating to traffic through waters, transportation of dangerous goods and special goods by sea, determination of hazardous and toxic waste, management of hazardous and toxic waste, navigation in sea transportation including aspects of shipping safety and security.